Al-Ukhuwah al-Ijtima’iyah wa al-Insaniyah: Kajian terhadap Pluralisme Agama dan Kerjasama Kemanusiaan - Hamidah Hamidah (Intizar, 2015)
The Results of this study discusses about religious pluralism and humanitarianism cooperation. The Paradigm of freedom and islamic consideration concern the doctrine of human equality. This equality can established the brotherhood and friendship between religions in social life based on humanity for the realization of social order together. To achieve religious harmony and inter-religious cooperation and harmonious and qualities, should be based on the factors and elements that are universal, ie factors and elements of humanity based on religious view. When the universal elements and factors that can be used effectively. Meanwhile, to realize the harmony of religious life and inter-religious cooperation requires elements and external factors, such as the state and the government.